HCV seropositivity in inmates and in the general population: an averaging approach to establish priority prevention interventions. Issue 10 (19th October 2014) - Roux, P; Sagaon-Teyssier, L; Lions, C; Fugon, L; Verger, P; Carrieri, M P
Abstract : Objectives: Despite the fact that a considerable portion of hepatitis C virus (HCV) positive individuals are viraemic, the risk of transmitting HCV to others is context dependent. Prison is a particularly risky environment as HCV prevention tools are often unavailable. Using data from a cross-sectional study conducted in centres for HCV testing in southeastern France, we aimed to compare the patterns of risk factors in HCV-positive inmates with those in the general population. Setting: 26 centres for HIV/HCV testing in southeastern France (23 in the general population and 3 in prison). Primary outcome measure: HCV seropositivity measured with ELISA test. Methods: A propensity score method to ensure that the general and inmate populations could be compared and a multimodel averaging to estimate the degree (strong, weak, none) of the association of a number of specific factors with HCV seropositivity in each group. Results: Among the 52 082 participants, HCV infection prevalence was 1.5% and 5.2% in the general (n=46 125) and inmate (n=5957) populations, respectively. In both populations, 'drug injection without snorting' and 'drug injection with snorting' were very strongly associated with HCV seropositivity. Among inmates, 'drug snorting alone' (OR (95% CI) 2.21 (1.39 to 3.52) was also a strong correlate while tattoos, piercings (OR (95% CI) 1.22 (0.92 to 1.61)) and the sharing of toiletry items (OR (95% CI) 1.44 (0.84 to 2.47)) were weak correlates. Conclusions: The pattern of risk factors associated with HCV seropositivity is different between the general and prison populations, injection and snorting practices being more prevalent in the latter. Access to prevention measures in prisons is not only a public health issue but also a human right for inmates who deserve equity of care and prevention.